2015
DOI: 10.3852/15-007
|View full text |Cite
|
Sign up to set email alerts
|

First comprehensive phylogenetic analysis of the genusErysiphe(Erysiphales, Erysiphaceae) I. TheMicrosphaeralineage

Abstract: The genus Erysiphe (including powdery mildew fungi only known as anamorph, Pseudoidium) is the largest genus in the Erysiphaceae and contains more than 50% of all species in this family. Little is known about the phylogenetic structure of this genus. We conducted a comprehensive phylogenetic analysis of the Microsphaera-lineage, a monophyletic group including species of sects. Microsphaera and Erysiphe, using 401 sequences of nuc ITS1-5.8S-ITS2 and the 28S rDNA regions. This analysis gave many small clades del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
84
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 52 publications
3
84
0
4
Order By: Relevance
“…A phylogeny inferred based on ITS sequence data obtained in this study together with 26 sequences from GenBank grouped our sequence in a clade composed of E. corylacearum collections from Corylus spp. including one specimen on C. avellana = KY082910.1 from Turkey (Sezer, Dolar, Lucas, Köse, & Gümüş, ), on C. sieboldiana = LC009928 (Japanese hazel) from Japan (Takamatsu, Ito Arakawa, Shiroya, Kiss, & Heluta, ), and two additional specimens on C. heterophylla = KR048061.1, JX880086.1 (Asian hazel) (Figure ). The sequences obtained in this study are available in GenBank with the accession number .…”
Section: Resultsmentioning
confidence: 99%
“…A phylogeny inferred based on ITS sequence data obtained in this study together with 26 sequences from GenBank grouped our sequence in a clade composed of E. corylacearum collections from Corylus spp. including one specimen on C. avellana = KY082910.1 from Turkey (Sezer, Dolar, Lucas, Köse, & Gümüş, ), on C. sieboldiana = LC009928 (Japanese hazel) from Japan (Takamatsu, Ito Arakawa, Shiroya, Kiss, & Heluta, ), and two additional specimens on C. heterophylla = KR048061.1, JX880086.1 (Asian hazel) (Figure ). The sequences obtained in this study are available in GenBank with the accession number .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the powdery mildew species on Quercus spp., viz., Erysiphe epigena , Erysiphe hypogena and Erysiphe quercicola were placed in sister clades. Recently, Takamatsu, Ito, Shiroya, Kiss, and Heluta () showed that the E. alphitoides clade phylogenetically includes powdery mildews from a wide range of host plants including Quercus spp. Therefore, the present powdery mildew on E. gunnii was tentatively identified as Erysiphe sp.…”
Section: Resultsmentioning
confidence: 99%
“…Erysiphe alphitoides is well‐known as oak powdery mildew fungus in Asia and Europe. However, recent studies showed that E. alphitoides also infects other tropical and non‐tropical trees and shrubs, viz., Mangifera indica, Sorbaria sorbifolia and Wisteria sinensis (Takamatsu et al., ). Furthermore, recent molecular phylogenetic studies show that some powdery mildew species have expanded their host ranges, for example Erysiphe hypophylla on Paeonia lutea, Erysiphe magnifica on Nelumbo nucifera and especially E. quercicola on Bauhinia purpurea, Cinnamomum camphora, Durio zibethinus , Murraya paniculata and Nephelium lappaceum (Farr & Rossman, ).…”
Section: Resultsmentioning
confidence: 99%
“…The robustness of the NJ trees was evaluated with 1000 bootstrap (BS) values. The NJ trees showed that the Korean isolates from S. stolonifera were placed in the E. aquilegiae clade, as defined by Takamatsu et al (2015) on the basis of ITS +28S rDNA data, with 99% and 100% BS value, respectively (Figs. 2 and 3).…”
mentioning
confidence: 99%
“…Therefore, further studies with morphological and molecular characterization are necessary to prove the taxonomic status of the species. Takamatsu et al (2015) performed molecular sequence analyses of Pseudoidium sp. on S. stolonifera and showed that the fungus pertains to the E. aquilegiae clade which comprises numerous morphologically defined powdery mildew species with insufficient resolution just based on ITS data.…”
mentioning
confidence: 99%